2005
DOI: 10.1063/1.1850363
|View full text |Cite
|
Sign up to set email alerts
|

A geometric approach to scalar field theories on the supersphere

Abstract: Following a strictly geometric approach we construct globally supersymmetric scalar field theories on the supersphere, defined as the quotient space $S^{2|2} = UOSp(1|2)/\mathcal{U}(1)$. We analyze the superspace geometry of the supersphere, in particular deriving the invariant vielbein and spin connection from a generalization of the left-invariant Maurer-Cartan form for Lie groups. Using this information we proceed to construct a superscalar field action on $S^{2|2}$, which can be decomposed in terms of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…In globally curved space an example of the use of graded Majorana spinors is obtained by considering field theories on the supersphere S 2|2 = UOSp(1|2)/U(1), as investigated in [11]. Graded Majorana spinors could also play an important role in the construction of supergravity theories.…”
Section: Discussionmentioning
confidence: 99%
“…In globally curved space an example of the use of graded Majorana spinors is obtained by considering field theories on the supersphere S 2|2 = UOSp(1|2)/U(1), as investigated in [11]. Graded Majorana spinors could also play an important role in the construction of supergravity theories.…”
Section: Discussionmentioning
confidence: 99%
“…6 It is reported that in scalar field theories on supersphere effective potentials are not generally bounded below, so the groundstates are not stable [20]. However, such problem cannot be applied to SUSY QHE, since the pseudo-potential Hamiltonian (3.15) has the lowest eigenvalue and the energies are bounded.…”
Section: The Spherical Susy Laughlin Wavefunction and Excitations [35]mentioning
confidence: 99%
“…Algebraic and topological structures of the fuzzy supersphere are well examined in [17,18]. Field theory models on supersphere have already been proposed; a non-linear sigma model and a scalar field model were explored in [19] and [20], respectively. Numerical calculations on fuzzy spaces have also been carried out (see [21] as a review).…”
Section: Introductionmentioning
confidence: 99%
“…This generalization is obtained in the course of developing a homological theory for supermanifolds. There are different supergeometric generalizations of the two-sphere S 2 , all of which are called superspheres [1][2][3]. These are useful models to study supersymmetry.…”
Section: Introductionmentioning
confidence: 99%